REFRAMING ISLAMIC WORLDVIEW IN YOUTUBE ESCAPE CONTENT OWNED BY @RAYMONDCHIN - Al Ghoni, Burhanudin; Hermawan, Ahmad; Irfanudin, Fahmi (Jurnal Asy-Syukriyyah, 2025)
This study analyzes how the Islamic worldview is reframed in Raymond Chin's YouTube Escape content and its impact on audience understanding. Using a qualitative method with a content analysis approach, data were collected from the videos on the channel. The study results show that the Escape channel has succeeded in reframing the Islamic worldview through a contemporary approach, diverse topics, active interaction with the audience, and engaging visual media. This approach improves the audience's understanding of Islam and helps eliminate negative stereotypes. Further discussions highlighted the challenges in ensuring the message's conformity with Islam's teachings. This study concludes that the Escape channel contributes significantly to spreading knowledge and building a positive image of Islam among the younger generation. More research is needed to explore the long-term impact of this content on audiences' religious understanding and practices.